Beyond the Classroom: The Intergenerational Effect of Incarceration on Children’s Academic and Nonacademic School-Related Outcomes in High School - McCauley, Erin (Socius, 2020)
The author uses strategic comparison regression and the Longitudinal Study of Adolescent to Adult Health (n = 11,767) to explore the effect of parental incarceration on academic and nonacademic outcomes in high school. This method compares youth whose parents were incarcerated before the outcomes are measured with those whose parents will be incarcerated after. The author examines most recent grades and a range of nonacademic outcomes, such as truancy, involvement in school activities, and suspension. Results indicate that the associations between parental incarceration and grades are largely accounted for by selection, but associations between parental incarceration and nonacademic processes persist. Maternal incarceration holds particular importance for behavioral outcomes (fighting and truancy), and paternal incarceration holds particular importance for behavioral, connectedness, and disciplinary outcomes. Researchers examining the intergenerational consequences of incarceration should examine school contexts beyond the classroom and explore the pathways through which this disadvantage occurs.